Language Acquisition of Children Age 4-5 Years Old in TK Dhinukum Zholtan Deli Serdang - Nurhasanah Purba; Mukramah; M. Wahyu Maulana; Gustia Ningsi (LingLit Journal Scientific Journal for Linguistics and Literature, 2020)
This study aims to determine the language acquisition of children aged 4-5 years. This research was conducted at TK Dhinukum Zholtan Medan which was conducted on March 4, 2020 with 4 students, 2 students aged 4 years and 2 students aged 5 years. In this study, researchers used the method of observation and also a questionnaire to collect data. Based on the description above, it can be concluded that children aged 5 and 4 years have different mastery. In addition to clear pronunciation, 5 year olds have mastery of more vocabulary and are able to describe things. Meanwhile, children aged 4 years have less vocabulary, have not been able to describe something and are not able to pronounce it clearly. This difference occurs because 5 year olds have already taken part in learning compared to 4 year olds. So that children aged 5 years are better able to communicate well, because they often interact with teachers and peers at school.